White Matter Tract Alterations in Drug-Naïve Parkinson's Disease Patients With Excessive Daytime Sleepiness - Ashraf-Ganjouei, Amir; Kheiri, Ghazaleh; Masoudi, Maryam; Mohajer, Bahram; Mojtahed Zadeh, Mahtab; Saberi, Pejman; Shirin Shandiz, Mehdi; Aarabi, Mohammad Hadi (Frontiers in Neurology, 2019)
Excessive daytime sleepiness (EDS) is relatively frequent in patients with Parkinson’s disease (PD), having a prominent burden on patients’ quality of life and causing dangerous events such as motor-vehicle accidents. Previous studies have indicated the role of certain neural tracts in the pathophysiology of sleep disturbances, especially in PD patients. We hypothesized that white matter integrity and connectivity might be altered in patients with PD and EDS. Therefore, this study investigated brain white matter microstructure alterations in patients with Parkinson’s disease with EDS (PD-EDS) compared to healthy controls and PD patients without EDS (PD-nEDS). Diffusion MRI connectometry was used to carry out group analysis between PD patients with and without EDS and healthy individuals. EDS in PD patients is associated with decreased connectivity in the left and right fornix, left and right inferior longitudinal fasciculus, left inferior and middle cerebellar peduncles in comparison to PD-nEDS group. These differences between PD-EDS and PD-nEDS patients reflects microstructural changes with respect to sleep-related circuits, which can pave the way for future investigations considering EDS pathogenesis in Parkinson’s disease.